Negative regulation of osteoclast precursor differentiation by CD11b and β2 integrin‐B‐cell lymphoma 6 signaling. (18th December 2012) - Park‐Min, Kyung‐Hyun; Lee, Eun Young; Moskowitz, Neal K; Lim, Elisha; Lee, Sun‐Kyeong; Lorenzo, Joseph A; Huang, Chuanxin; Melnick, Ari M; Purdue, P Edward; Goldring, Steven R; Ivashkiv, Lionel B
Abstract Negative regulation of osteoclastogenesis is important for bone homeostasis and prevention of excessive bone resorption in inflammatory and other diseases. Mechanisms that directly suppress osteoclastogenesis are not well understood. In this study we investigated regulation of osteoclast differentiation by the β2 integrin CD11b/CD18 that is expressed on myeloid lineage osteoclast precursors. CD11b‐deficient mice exhibited decreased bone mass that was associated with increased osteoclast numbers and decreased bone formation. Accordingly, CD11b and β2 integrin signaling suppressed osteoclast differentiation by preventing receptor activator of NF‐κB ligand (RANKL)‐induced induction of the master regulator of osteoclastogenesis nuclear factor of activated T cells, cytoplasmic 1 (NFATc1) and of downstream osteoclast‐related NFATc1 target genes. CD11b suppressed induction of NFATc1 by the complementary mechanisms of downregulation of RANK expression and induction of recruitment of the transcriptional repressor B‐cell lymphoma 6 (BCL6) to the NFATC1 gene. These findings identify CD11b as a negative regulator of the earliest stages of osteoclast differentiation, and provide an inducible mechanism by which environmental cues suppress osteoclastogenesis by activating a transcriptional repressor that makes genes refractory to osteoclastogenic signaling. © 2013 American Society for Bone and Mineral Research